O teście równości wariancji wykorzystującym metodę bootstrap - Kończak, Grzegorz (On the bootstrap test of homogenity variances, 2006)
The assumption of homogeneity of variance is supposed in various statistical methods such as ANOVA, discriminant analysis, cluster analysis, etc. The paper presents a test for homogeneity of variance using bootstrap methods that does not rely on normal distribution assumption. There are presented analytical results and the results of Monte Carlo study. There are compared the proposed test and classical Hartley’s homogeneity variance test.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 543-552